The End of the World as We Know It?: American Exceptionalism in an Age of Disruption. Issue 4 (21st September 2017) - Torpey, John
Abstract : This essay explores the recent election of President Donald J. Trump against the background of the idea of American exceptionalism. It posits that there have been a variety of versions of the notion of exceptionalism, one of which involves the question, "Why is there no fascism in the United States?" It argues that Trump may render invalid the assumption behind that question and that at best during his tenure we are likely to have a continuation of the "bad exceptionalism" associated with the question, "Why is there no socialism in the United States?"